(untitled) (Bangladesh Pharmaceutical Journal, 2019)
In this present investigation, gastroretentive mucoadhesive microspheres of Repaglinide was formulated, characterized and optimized by applying the design of experiment (DoE) for better release profile and sustain action of the drug. Solvent evaporation technique was used to prepare microspheres, where Methocel K15M CR (X1), Eudragit L 100 (X2) and rpm (X3) were used as independent variables whereas percent cumulative drug release at 8 hours (Y1), bond strength (Y2) and swelling at 8 hours (Y3) were used as dependent variables. Particle size, surface morphology, mucoadhesive bond strength, swelling study, and drug entrapment efficiency were determined to characterize the prepared microspheres. In vitro dissolution study was performed in 0.1N HCl (pH 1.2) media for 8 hours. Response surface of dependent variables was calculated by design expert software and it was found that most of the responses were fitted to the quadratic model. Percent cumulative drug release at 8 hours was found minimum 61.34% and maximum 87.29%, the minimum and maximum range of mucoadhesive bond strength was found 426.02 to 13335.74 N/m2 and in case of swelling at 8 hours, it was found 157.43 and 230.22%. After analyzing the responses, proposed formula was obtained from which minimization of percent cumulative drug release at 8 hours as well as swelling and maximization of bond strength was obtained. Thermal behavior was investigated by DSC study and no interaction was found between drug and excipients from FTIR study. Bangladesh Pharmaceutical Journal 22(2): 135-145, 2019